VD_FINDINFO Arrêt / 2018 / 25 vom 8. Januar 2018 - VD Tribunal cantonal (2018)
ASSURANCE POUR SOINS DENTAIRES, ASSURANCE-MALADIE PRIVÉE | 31 al. 1 LAMal, 33 al. 2 LAMal, 33 al. 5 LAMal, 33 let. a OAMal, 17 OPAS